Contribution to the treatment of dysfunctional metrorrhagia - Arenas, Normando (2015)
It insists on the correct diagnosis of dysfunctional metrorrhagia and considers their treatment in two phases. In the phase of scraping the uterine bleeding employ, preparations with tri-gonadal steroids and toluidine blue. Scraping what we make almost systematically, as a treatment and as a diagnostic tool that will guide us for future therapy. With the tri-gonadal steroids have stopped 94% of bleeding. Toluidine blue we indicated only when the title protamine cg exceeds 0.14. blood, that we have observed in 35% of our patients. After the treatment period of bleeding depends on the histology of the endometrium. In the proliferative or hyperplastic endometrium will attempt to correct the phase cycle. By hormonal means or roentgenoterápicos: In the secretory endometrium it is advisable to wait, often for no recurrence metrorrhagia after scaling. Otherwise we administer progesterone in the second phase. In atrophic endometrium and telengiectásicos observed at menopause, estrogen administered in small doses and for prolonged periods to improve the trophism of the uterine lining.